DARI LITERASI MENUJU KEBERADABAN DIGITAL: REKONSTRUKSI ETIKA WARGA NEGARA DIGITAL INDONESIA 2020-2026 - Recy Harviani Zurwanty; Sri Rahayu; Fatimatuz Zahrah (Smart Education, 2026)
Abstract: Internet penetration in Indonesia continues to increase, but this has not been matched by responsible digital behavior. This study analyzes the development of digital ethics research in Indonesia from 2020 to 2026 through a qualitative literature review with Braun and Clarke's thematic analysis of 34 articles purposively selected from Google Scholar, Crossref, Garuda, DOAJ, and SINTA. Coding was conducted using NVivo 14, while the validity of the findings was strengthened through source triangulation, audit trails, and peer debriefing. The analysis identified four interrelated themes: the normalization of unethical behavior such as cyberbullying and plagiarism; low digital reasoning that accelerates the spread of disinformation; the dilemma between freedom of expression and digital responsibility; and the reconstruction of ethics through strengthening digital literacy and citizenship. Weak digital reasoning has been shown to reinforce unethical behavior while hindering the formation of a responsible digital culture. This study concludes that the challenges of digital ethics in Indonesia are rooted in socio-cultural factors, so strengthening them requires ongoing collaboration between the government, educational institutions, platform providers, and the community.